THE ROLE OF MARKETING STRATEGIES IN THE DEVELOPMENT OF THE CREATIVE ECONOMY IN THE CULINARY SUB-SECTOR: A SYSTEMATIC LITERATURE REVIEW - Nurul Muthma Inna; Putri Ayu Fitriyani; Tria Wulansari; Muh Ilyas Khalid Alfadly (BEMJ: Business, Entrepreneurship, and Management Journal, 2025)
This study aims to systematically map research on MSME-based culinary businesses with a focus on marketing and innovation through a Systematic Literature Review approach. The findings indicate that digital marketing and product innovation are dominant themes that significantly contribute to competitiveness, business performance, and sustainability in the culinary sector. This study produces an integrated conceptual map linking culinary business, marketing, innovation, and small enterprises. The results are expected to serve as both theoretical and practical references for the development of adaptive and sustainable culinary MSME strategies in response to market and technological dynamics.